Allergen immunotherapy in MASK-air users in real-life - Sousa-Pinto, Bernardo (2022)
Funding Information: MASK-air has been supported by Charit? Universit?tsmedizin Berlin, EU Grants (EU Structural and Development Funds, POLLAR: EIT Health POLLAR, EIT Health Twinning) and educational grants from Mylan-Viatris, ALK, GSK, Novartis and Uriach. Open access funding enabled and organized by Projekt DEAL. Publisher Copyright: © 2022 The Authors. Clinical and Translational Allergy published by John Wiley & Sons Ltd on behalf of European Academy of Allergy and Clinical Immunology.